Evaluation of the productive quality for processing the frozen fruit pulps - Sebastiany, Estela (2010)
In Roraima State, the local frozen fruit pulps producers employ artesanal procedures which do not ensurethe quality of the final products; even so, this agroindustry segment has been increasing and predominaltyamong the small companies. The quality of frozen fruit pulps production in Boa Vista/RR was assessedby a technical visit and applying a check list at four selected companies proccessing in natura fruit pulps.Inadequate frozen fruit pulps productive processing at local industries was evidenced, thus being innoncompliace with the legislation in force.